The “Silent Enemy” Called Renal Artery Stenosis: A Mini-Review - José Silva; Juan Tonheiro; Fernanda Rodrigues (Journal of Vascular Diseases)
Renal artery stenosis (RAS) is a vascular condition characterized by narrowing of one or both renal arteries, leading to reduced blood flow to the kidneys, activation of the renin–angiotensin–aldosterone system (RAAS), and subsequent renovascular hypertension. Overactivation of the same cascade potentiates the production of angiotensin II, which induces systemic vasoconstriction, increases sodium and water retention via aldosterone, and activates the sympathetic nervous system. Angiotensin II is also implicated in endothelial dysfunction, oxidative stress, and chronic inflammation, thus impairing vascular remodeling and arterial stiffness, all of which serve to accelerate cardiovascular complications, such as left ventricular hypertrophy, heart failure, and myocardial infarction. RAS is usually due in at least 90% of cases to atherosclerosis, which typically affects older people with diabetes and smoking as risk factors. There are two types of RAS: unilateral and bilateral. Bilateral RAS is commonly associated with flash pulmonary edema, a life-threatening emergency condition in which alveolar space flooding can occur within minutes. RAS typically remains asymptomatic until the late stage with complications of hypertension, ischemic nephropathy, or chronic kidney disease. FMD tends to create structural abnormalities of the artery, whereas atherosclerosis causes plaque formation and endothelial dysfunction of the artery. Epidemiological surveys have revealed that the prevalence of RAS ranges from 4% to 53% and is especially high among patients with hypertension, cardiovascular disease, or CKD. Diagnosis is based on clinical suspicion and supported by imaging studies, including Doppler ultrasound, computed tomography angiography, and magnetic resonance angiography. Early detection also relies on certain laboratory biomarkers, especially in identifying high-risk patients. These markers would include increased plasma renin activity, elevated aldosterone-renin ratio, and inflammatory markers, including C-reactive protein and endothelin-1. Treatment would also involve pharmacological approaches, including RAAS inhibitors, beta-blockers, and statins, and interventional treatments, including angioplasty and stenting in patients with severe forms of the disease. However, the Cardiovascular Outcomes in Renal Atherosclerotic Lesions (CORAL) Trial showed that most patients would likely require medical therapy, and that intervention should be reserved for those with uncontrolled hypertension, progressive renal dysfunction, or recurrent episodes of pulmonary edema. Other emerging therapies include drug-eluting balloons, bioresorbable stents, and gene-editing techniques, all of which have shown great promise in the few studies that have been conducted, although further evaluation is needed. Despite these advances, there are still gaps in knowledge regarding patient stratification, biomarker validation, and the development of personalized treatment strategies. This article reviews the complexities of RAAS and its systemic impact on cardiovascular and renal health. Future research can therefore focus on improving early diagnosis, optimizing patient selection for intervention, and developing new therapies to slow disease progression and mitigate complications.